Using telehealth to teach valued skills to adults with intellectual and developmental disabilities. Issue 3 (15th June 2020) - Pellegrino, Azure J.; DiGennaro Reed, Florence D.
Abstract : Telehealth uses electronic information and telecommunication technologies to deliver long‐distance clinical services. It has successfully been used by clinical professionals to teach family and staff members to provide evidence‐based assessment and treatment procedures. There is no research to date, however, evaluating the use of telehealth to directly teach individuals with intellectual and developmental disabilities (IDD). Thus, we evaluated the efficacy of a telehealth intervention using total task chaining with least‐to‐most prompting delivered via videoconference to 2 adults with IDD. Both participants demonstrated low independent responding during baseline with enhanced written instructions present. During intervention, which included vocal and model prompting, both participants met the mastery criterion for each skill in fewer than 15 sessions, which maintained after 2 weeks. Finally, both participants expressed satisfaction with the goals, procedures, and effects of the intervention. We discuss the broader scope of the intervention for individuals with disabilities when face‐to‐face services may not be feasible.